Künstler in Köln 1990 - Nestler, Peter; Dinges, Christiane; Gellner, Winfried; Hüllenkremer, Marie; Arthotek der Stadtbücherei, Köln; BBK (Berufsverband Bildender Künstler, Köln; GEDOK; Kölnischer Kunstverein, Köln; Kulturamt Köln; Museum Ludwig, Köln (Köln : Wienand Verlag, 1989)
Adamski, Hans-Peter ; Agnes, Julius ; Agricola, W.O.F. ; Bandau, Joachim ; Barner, Herm-Jörg ; Barnim, Peter H. ; Bergheim, Magdalena ; Bergler, Raphaele ; Blume, Bernhard Johannes ; Blumenberg, Olga ; Brügger, Susanne ; Brummack, Heinrich ; Cürten, Gregor ; Cürten, Günter ; etc
boek
Keywords: Duitsland; Keulen